Antibiofilm Activity of Ethanolic Extract of Zingiber officinale against Aggregatibacter actinomycetemcomitans ATCC 43718 (serotype B) - Putri Cahaya Situmorang; Dian Eka Ermawati; Nindita Clourisa Amaris Susanto; Diyah Tri Utami; Heru Sasongko; Sholichah Rohmani; M Fiqri Zulpadly; Anif Nur Artanti; Ulfa Afrinurfadhilah Darojati; Annisa Diyan Meitasari; Meta Kartika Untari (Institut Pertanian Bogor, 2026)
Red ginger plays a role in bacterial infection, diarrhea, and cough. Therefore, this study aims to evaluate the ethanolic extract of Zingiber officinale for its antibiofilm activity against Aggregatibacter actinomycetemcomitans ATCC 43718 (serotype B). The extraction process of Zingiber officinale is carried out by maceration. An antibiofilm activity assay was used with the dilution method with the various formulas of 20;10;5;2,5;1,25 % w/v. The biofilm inhibition concentration (MBIC50) was calculated. The SEM analysis was conducted to evaluate biofilm bacterial growth after the treatment. The data was then analyzed with IBM SPSS Statistics version 21.0 using one-way ANOVA (Analysis of Variance). The results showed that the ethanolic extract of Zingiber officinale had an inhibitory effect on A. actinomycetemcomitans ATCC 43718 (serotype B). This proved that the biofilm bacterial growth was effectively inhibited by the chemical compound of red ginger. The extracellular polymeric substance (EPS) matrix degraded after treating the cell biofilm. It can be concluded that the ethanolic extract of Zingiber officinale has potential against A. actinomycetemcomitans. Further research is needed to determine the safety and efficacy of A. actinomycetemcomitans ATCC 43718 (serotype B) can be developed as an alternative antibiofilm